Critical questions in ovarian cancer research and treatment: Report of an American Association for Cancer Research Special Conference. Issue 12 (5th March 2019) - Bast, Robert C.; Matulonis, Ursula A.; Sood, Anil K.; Ahmed, Ahmed A.; Amobi, Adaobi E.; Balkwill, Frances R.; Wielgos‐Bonvallet, Monicka; Bowtell, David D. L.; Brenton, James D.; Brugge, Joan S.; Coleman, Robert L.; Draetta, Giulio F.; et al.
Abstract : Substantial progress has been made in understanding ovarian cancer at the molecular and cellular level. Significant improvement in 5‐year survival has been achieved through cytoreductive surgery, combination platinum‐based chemotherapy, and more effective treatment of recurrent cancer, and there are now more than 280, 000 ovarian cancer survivors in the United States. Despite these advances, long‐term survival in late‐stage disease has improved little over the last 4 decades. Poor outcomes relate, in part, to late stage at initial diagnosis, intrinsic drug resistance, and the persistence of dormant drug‐resistant cancer cells after primary surgery and chemotherapy. Our ability to accelerate progress in the clinic will depend on the ability to answer several critical questions regarding this disease. To assess current answers, an American Association for Cancer Research Special Conference on "Critical Questions in Ovarian Cancer Research and Treatment" was held in Pittsburgh, Pennsylvania, on October 1‐3, 2017. Although clinical, translational, and basic investigators conducted much of the discussion, advocates participated in the meeting, and many presentations were directly relevant to patient care, including treatment with poly adenosine diphosphate ribose polymerase (PARP) inhibitors, attempts to improve immunotherapy by overcoming the immune suppressive effects of the microenvironment, and a better understanding of the heterogeneity of the disease. Abstract : An American Association for Cancer Research special conference considered critical questions in ovarian cancer research and management. Abnormalities in the cancer genome, gene expression, microenvironment, metabolism, and immunity have provided targets to improve early detection, targeted therapy, and immunotherapy.